A developmental approach to cyberbullying: Prevalence and protective factors. (March 2019) - Kowalski, Robin M.; Limber, Susan P.; McCord, Annie
Abstract: Recent years have witnessed a plethora of research on cyberbullying. However, many of the published studies have yielded mixed findings related to cyberbullying and its relation to demographic variables such as age, sex, and race/ethnicity. Review papers have been published on some of these topics, but comprehensive reviews of the relation between age and cyberbullying victimization and perpetration are lacking, particularly with regard to protective factors. Thus, the current paper takes a developmental approach to examine age and cyberbullying. The review focuses specifically on age variations in technology use, prevalence of cyberbullying involvement, risk and protective factors, and outcomes. Directions for future research, including implications for prevention and intervention, are discussed. Highlights: A developmental approach to ICT use and cyberbullying is discussed. Cyberbullying risk and protective factors across ages are examined. Notable gaps in the literature are highlighted, specifically among elementary school age youth and adults.